Effects of Fundamental Frequency and Vocal Tract Resonance on Sentence Recognition in Noise. - Jing Yang; A. Xianhui Wang; Victoria Costa; Li Xu (Journal of Speech, Language & Hearing Research, 2025)
Purpose: This study examined the effects of change in a talker's sex-related acoustic properties (fundamental frequency [F0] and vocal tract resonance [VTR]) on speech recognition in noise. Method: The stimuli were Hearing in Noise Test sentences, with the F0 and VTR of the original male talker manipulated into four conditions: low F0 and low VTR (LF0LVTR; i.e., the original recordings), low F0 and high VTR (LF0HVTR), high F0 and high VTR (HF0HVTR), and high F0 and low VTR (HF0LVTR). The listeners were 42 English-speaking, normal-hearing adults (21--31 years old). The sentences mixed with speech spectrum--shaped noise at various signal-to-noise ratios (i.e., -10, -5, 0, and +5 dB) were presented to the listeners for recognition. Results: The results revealed no significant differences between the HF0HVTR and LF0LVTR conditions in sentence recognition performance and the estimated speech reception thresholds (SRTs). However, in the HF0LVTR and LF0HVTR conditions, the recognition performance was reduced, and the listeners showed significantly higher SRTs relative to those in the HF0HVTR and LF0LVTR conditions. Conclusion: These findings indicate that male and female voices with matched F0 and VTR (e.g., LF0LVTR and HF0HVTR) yield equivalent speech recognition in noise, whereas voices with mismatched F0 and VTR may reduce intelligibility in noisy environments.